2021
DOI: 10.1002/fsn3.2665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clover sprouts protein hydrolysates as an egg substitute on physicochemical and sensory properties of mayonnaise

Abstract: Mayonnaise is a semi‐solid oil‐in‐water emulsion that in addition to eggs other stabilizers and thickeners are used as emulsifiers for better stability. Although eggs are an important ingredient in the production of mayonnaise, the health problems associated with the use of eggs is increasing due to their high cholesterol content. The aim of this study was to evaluate the feasibility of clover sprout protein hydrolysates (CSPH) to replace eggs for the production mayonnaise. First, CSPH was produced using alcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…DSF-SC, which has a larger protein concentration than CSF, appears to exhibit higher hydrophobicity, improving adsorption capacity at the droplet surface and thereby boosting emulsion capability. In clover protein mayonnaise, higher emulsion capacity and stability were reported compared to EY mayonnaise, and increasing clover protein substitution was found to enhance the stability of the mayonnaise [12]. Similarly, The mayonnaise containing wheat germ protein exhibited higher emulsion capacity and stability than the control group, consistent with the findings of this study [40].…”
Section: Emulsion Capacity and Stabilitysupporting
confidence: 87%
See 1 more Smart Citation
“…DSF-SC, which has a larger protein concentration than CSF, appears to exhibit higher hydrophobicity, improving adsorption capacity at the droplet surface and thereby boosting emulsion capability. In clover protein mayonnaise, higher emulsion capacity and stability were reported compared to EY mayonnaise, and increasing clover protein substitution was found to enhance the stability of the mayonnaise [12]. Similarly, The mayonnaise containing wheat germ protein exhibited higher emulsion capacity and stability than the control group, consistent with the findings of this study [40].…”
Section: Emulsion Capacity and Stabilitysupporting
confidence: 87%
“…Consequently, research is actively underway to explore and develop emulsifiers that can replace EY in mayonnaise production [5,6]. Constant research efforts are being done to develop mayonnaise with plant-based ingredients such as wheat protein mayonnaise [7], soy milk mayonnaise [8], pea mayonnaise [9], chickpea, faba bean, lentil mayonnaise [10], aquafaba mayonnaise [11], and clover sprouts mayonnaise [12].…”
Section: Introductionmentioning
confidence: 99%
“…This result was consistent with when clover sprouts protein hydrolysate and soybean oil body were used as egg substitutes in mayonnaise. As the concentration of the substitute increased, sensory scores consistently decreased [56]. However, the comprehensive acceptability scores of SO5:FMP25 and SO5:FMP0 were not significantly different (p > 0.05).…”
Section: Sensory Evaluationmentioning
confidence: 90%
“…Oil droplet size distribution, firmness, consistency, storage modulus (G0), and yield stress were influenced by the type of oil used [4] [5]. Mayonnaise is a semi-solid oil-in-water emulsion in which, in addition to eggs, other stabilizers and thickeners are used as emulsifiers for better stability [6] [7]. The earlier study's findings demonstrated a high potential for using VCO in mayonnaise production to improve the product's biological functions, but emulsion stability still needs to be improved.…”
Section: Introductionmentioning
confidence: 99%